A Surgical Case of Venous Aneurysm of the Cephalic Vein with Unique Clinicopathological Findings for Venous Dissection: A Possible New Entity. (30th June 2018) - Kobata, Takashi; Yamada, Sohsuke; Mizutani, Ken-ichi; Kurose, Nozomu; Takagi, Sho; Machida, Yuichiro; Kanda, Tsugiyasu
We presented an extremely rare case of a 38-year-old female's venous aneurysm of left cephalic vein with unique histopathological features, displaying variably thinned medial wall with focal, markedly reduced or absent smooth muscle cells and elastic fibers, most likely leading to the venous dissection with an intimal tear and many medial blood-filled vascular channels. We propose that those venous dissection-like findings would be a new feature especially from the clinicopathological viewpoints and might be considered in the classification of venous aneurysm. Further prospective studies are needed to validate the presence and significance of venous dissecting aneurysm as a new histopathological entity, after collecting and investigating a larger number of venous aneurysm cases examined. This short report could interest the scientific community, taken together with potentially specific findings of new entity, venous dissecting aneurysm.